RNA Fibers as Optimized Nanoscaffolds for siRNA Coordination and Reduced Immunological Recognition. (9th October 2018) - Rackley, Lauren; Stewart, Jaimie Marie; Salotti, Jacqueline; Krokhotin, Andrey; Shah, Ankit; Halman, Justin R.; Juneja, Ridhima; Smollett, Jaclyn; Lee, Lauren; Roark, Kyle; Viard, Mathias; Tarannum, Mubin; et al.
Abstract: RNA is a versatile biomaterial that can be used to engineer nanoassemblies for personalized treatment of various diseases. Despite promising advancements, the design of RNA nanoassemblies with minimal recognition by the immune system remains a major challenge. Here, an approach is reported to engineer RNA fibrous structures to operate as a customizable platform for efficient coordination of siRNAs and for maintaining low immunostimulation. Functional RNA fibers are studied in silico and their formation is confirmed by various experimental techniques and visualized by atomic force microscopy (AFM). It is demonstrated that the RNA fibers offer multiple advantages among which are: i) programmability and modular design that allow for simultaneous controlled delivery of multiple siRNAs and fluorophores, ii) reduced immunostimulation when compared to other programmable RNA nanoassemblies, and iii) simple production protocol for endotoxin‐free fibers with the option of their cotranscriptional assembly. Furthermore, it is shown that functional RNA fibers can be efficiently delivered with various organic and inorganic carriers while retaining their structural integrity in cells. Specific gene silencing triggered by RNA fibers is assessed in human breast cancer and melanoma cell lines, with the confirmed ability of functional fibers to selectively target single nucleotide mutations. Abstract : RNA nanotechnology provides a unique platform for the treatment of various maladies. Here, fibrous RNA structures are engineered, which are capable of simultaneous and precise silencing of different genes present in human cancer cell lines. These RNA structures are demonstrated to be compatible with several delivery agents and exhibit both highly tunable immunogenicity as well as enhanced ease of production.